2020
DOI: 10.1038/s41531-020-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Speech-based characterization of dopamine replacement therapy in people with Parkinson’s disease

Abstract: People with Parkinson’s (PWP) disease are under constant tension with respect to their dopamine replacement therapy (DRT) regimen. Waiting too long between doses results in more prominent symptoms, loss of motor function, and greater risk of falling per step. Shortened pill cycles can lead to accelerated habituation and faster development of disabling dyskinesias. The Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) is the gold standard for monitoring Parkinson’s disease progression but requires a neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 66 publications
3
46
1
Order By: Relevance
“…Yet, while we targeted PD patients on levodopa, as in previous works, 25 semantic alterations in this disease are sensitive to medication status. 44 New studies should explore whether the deficits observed in ADD remain specific when considering PD patients with varying levels of dopamine bioavailability. Still, our findings suggest that theoretically informed semantic measures may prove useful not only to identify specific brain diseases, but also to discriminate among them.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, while we targeted PD patients on levodopa, as in previous works, 25 semantic alterations in this disease are sensitive to medication status. 44 New studies should explore whether the deficits observed in ADD remain specific when considering PD patients with varying levels of dopamine bioavailability. Still, our findings suggest that theoretically informed semantic measures may prove useful not only to identify specific brain diseases, but also to discriminate among them.…”
Section: Discussionmentioning
confidence: 99%
“…Attention and memory impairments in PD are risk factors for dysarthric manifestations, 29 which, in turn, can predict cognitive decline 16,23 . Because MCI is present in 25%–57% of cases, 48‐50 the diversity of speech disturbances might partly reflect cognitive heterogeneity.…”
mentioning
confidence: 99%
“…Action-semantic alterations are paramount among the communicative profile of PD patients [13,16,17] and they constitute candidate cognitive markers for early PD [6,17]. Intake of levodopa or dopamine agonists seems to favor verbal action fluency [12,106] and action description in spontaneous speech [13], but such pharmacological interventions may have undesirable side effects. Promisingly, atDCS might circumvent some of such consequences and last for substantial time periods [36,57,[107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%